The Role of Cost and Benefit Techniques in Developing Supply Chain Management Models in the Transportation System (Analytical and Practical Study at Baghdad International Airport) - Mu'ayyed Abdul Husain Al-Fadl; Arshad Abdul Amir Jassem Al Shammari (International Journal of Supply Chain Management, 2019)
In a dynamic environment developed by information technology and the accompanying communications devices and modern movements made the world a small village characterized by sharp economic and political fluctuations and financial coincided with the beginning of the twentieth century.It made the investment environment represented by financial resources and their supply chain management play a prominent role in influencing the financial policy of business organizations whether productive or service.It required decision makers to work hard to obtain returns and the lowest possible costs as they pose a clear threat to investment activity because of their impact on the rise or fall in those revenues which he hopes to obtain because of these fluctuations.In the business we must recognize these fluctuations in order to face them in general and work to find methods to be used to ensure the achievement of what aspires to access, and perhaps linear programming using the software ready Q.S.B and TORA.In the current competitive era, the goal of creating a supply chain is to increase the operational effectiveness, profitability, and ability of the organization to compete with supply chain partners, also companies need to focus on their capabilities and resources in order to gain competitive advantage and improve their market position. In fact, the competitiveness of manufacturing companies relies on the development of their competencies. Meanwhile, supply chain management is considered as a powerful tool for promoting corporate growth and creating competitive advantage. Supply chain management operations play a critical role in management decisions, as far as they can have significant effects on corporate profitability and operational success.This study was designed to shed light on how to transform the transfer problem into linear programming that can be obtained for each variable of the decision maker in the supply chain management.The analysis of these returns using manual solutions and ready-made software referred to above in light of the data obtained for the sample of the study of the civil aviation authority and the air cargo, sea and land at the level of Iraqduring the month of April 2018. The study concluded a number of conclusions, the most important is that the best for the airline to rely on ready-made software if it wants to be rational decisions instead of relying on manual solutions.The study came out with a number of recommendations, perhaps the most important of which is the need to establish a special computer lab to process the data and extract the results by the airport administration and the employees of the Iraqi Airways Company which is the advantage that the decision maker can not succeed without.